Introduction to maintenance, repair and overhaul of aircraft, engines and components - Weerasekera, Shevantha (SAE deep dive, 2020)
Introduction to Maintenance, Repair and Overhaul of Aircraft, Engines and Components brings together the basic aspects of a fundamentally important part of the aerospace industry, the one that supports the global technical efforts to keep passenger and cargo planes flying reliably and safely. Over time, aircraft components and structural parts are subject to environmental effects, such as corrosion and other types of material deterioration, wear and fatigue. Such parts could fail in service and affect the safe operation of the aircraft if the degradation were not detected and addressed in time. Regular planned maintenance supports the current and future value of the aircraft by minimizing the physical decline of the aircraft and engines throughout its life. Introduction to Maintenance, Repair and Overhaul of Aircraft, Engines and Components was written by the industry veteran, Shevantha K. Weerasekera, an aerospace engineer with 20+ years of aircraft maintenance experience, who currently leads the engineering team of a major technical enterprise in the field.